Analisis sitasi pada jurnal berkala arkeologi menggunakan aplikasi “Publish or Perish” - Saputro, Bayu Indra (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2022)
Purpose. This article explains how to determine the quality of a scientific journal by analyzing the level of citation in Berkala Arkeologi journal articles.Methodology. The method used is bibliometric analysis which aims to determine the distribution of citations in an article document in a journal. The data source of this research is Berkala Arkeologi articles for the period of 42 years between 1980 and 2022 which were downloaded using the Publish or Perish 7 application.Results and discussion. The most prolific authors in publishing articles in the journal Berkala Arkeologi are Indah Asikin and T.M Hari Lelono with 24 articles. While the article written by Ph. Subroto has the highest citation among other articles, namely 25 citations. The Journal of Archaeology also publishes articles in a timely manner.Conclusion. Journal Berkala Arkeologi has implemented the periodicity of articles published on time and applies open access. The most prolific authors in publishing articles in the journal Berkala Arkeologi are Indah Asikin and T.M Hari Lelono with 24 articles. While the article written by Ph. Subroto with the title Zonal Patterns of Archaeological Sites published in 1995 turned out to have the highest number of citations among other articles. Thus, the number of articles published by the author is inversely proportional to the number of citations. But this proves that the article still has an influence in the development of archaeology.